Updating Critical Discourse Analysis in Education - Erica Newhouse (Networks: An Online Journal for Teacher Research, 2014)
The publication of the second edition of Rogers’ An Introduction to Critical Discourse Analysis in Education is timely and relevant to the current social, political, and educational climate. Rogers’ text provides an in-depth introduction to critical discourse analysis (CDA) in education, an understanding of how the education “crisis” has been constructed, and the possibilities for researchers to use this approach to interrupt these “naturalizations.” This edition reflects changes in the field with the addition of Gunther Kress’ multimodal social semiotic approach to discourse analysis, which opens new areas of investigation and critique.